Log in to add a comment

Log in to add a comment

let

α andβ are the roots

soα = -3 and β = 7

general form of equation with α and β as roots is[ x²-(α+β)x +αβ] = 0 where k is constant

substituting the α and β values ,x²-(-3+7)x+(-3×7)

⇒x²-(4)x+(-21)= 0

x²-4x-21 = 0 is the quaquadratic equation whose root are and -3 and 7

α and β are the zeroes of the quadratic equation,

then the equation will be k[ax² -(α+β)x +αβ]

α = -3

β = 7

α+β = 4

αβ = -21

k[x² -(α+β)x +αβ] = k[x² -4x -21]

let k = 1

then the quadratic equation will be x² -4x -21 = 0